PERTUNJUKAN WAYANG KULlT: WISATA MANDALA KESADARAN KOSMIS - I Nyoman Murtana (Gelar : Jurnal Seni Budaya, 2011)
The domain of intellectual and empirical consciousness analyzing wayang as a thinking subject shows that the reality of wayang realm is the formation of human thought. On the contrary, empiricism understands human consciousness in wayang as the reflection on an objective fact beyond the thought. That is why, the reality of wayang itself can be understood objectively as far as it is reflected on consciousness. However, the performance is intended for the emotional domain to develop the human imaginative power of nature. The domain of nature and that of human being in wayang develops cultural consciousness, the position of human being in the universe and the position of nature for human life, both in horizontal and vertical dimensions excreted in wayang kulit performance. The domain of ontological function has something to do with the difference between the manifest function and the latent function (visible and invisible functions) of wayang kulit performance. The manifest function is an objective consequence of adapted system demanded and realized by partisans of that system. On the contrary, the latent function is the objective consequence of wayang kutlt performance undesired and unrealized by community members.  The domain of entertainment and of rite converging in wayang kullt performance review the duality of social function of wayang kulit performance. On the one hand wayang kulit performance has the  function of entertainment and on the other hand it has a spiritual mission to meet a part of human necessities of sacred life.Key words: tourism, nature, human being, wayang kulit performance.